Genetic diversity, phylogenetic relationships and systematic revision of some Delimini (Gastropoda, Clausiliidae) from Mid-Mediterranean areas: new insights and biogeographic considerations - M. Colomba; S. Reale; A. Gregorini; S. Scibetta; A. Reitano; R. Viviano; W. De Mattia; F. Liberto; S. Surdo; I. Sparacio (The European Zoological Journal)
The genetic diversity of some representative taxa of the door snail tribe Delimini R. Brandt, 1956 (Clausiliidae) from the Mid-Mediterranean areas was investigated. The analysis was carried out on 60 cytochrome oxidase subunit I (COI) partial sequences from the genera Mauritanica O. Boettger, 1879; Sicania Tomlin, 1929; Siciliaria Vest, 1867; and Stigmatica O. Boettger, 1877 combined with 51 homologous sequences available for the same tribe retrieved from GenBank. Moreover, the shell and genital morphology of a few selected taxa were examined to redefine their systematic position. Key topics can be summarized as follows: (i) a revision of the phylogenetic relationships among Mauritanica, Sicania, Siciliaria, and Stigmatica is discussed; (ii) the new monospecific genus Benoitiella gen. n. is proposed for Mauritanica scarificata from the island of Marettimo; (iii) Mauritanica cossoni is re-allocated to the genus Siciliaria; (iv) within the genus Siciliaria, S. septemplicata and S. leucophryna revealed a more significant heterogeneity than expected so far; (v) Siciliaria leucophryna nordsiecki n. ssp. is described; (vi) a new systematics of the Siciliaria alcamoensis group is proposed; (vii) Siciliaria a. vigil n. ssp. and S. a. aegestana n. ssp. are described; (viii) the timing of the Delimini radiation in the Mediterranean is explored; and (ix) some biogeographic hypotheses on the origins and evolution of the taxa under study are suggested.